2015
DOI: 10.1007/s40268-015-0087-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Modified Saquinavir/Ritonavir Dosing Regimen with Lower Dose Lead-In Phase on QTc Interval, Pharmacokinetics, Antiviral Activity and Safety in Treatment-Naïve HIV-1-Infected Patients

Abstract: BackgroundSaquinavir/ritonavir (1000/100 mg twice daily [BID]) is associated with dose- and exposure-dependent prolongation of the QT interval. The QT risk is considered higher during the first week of therapy, when saquinavir peak exposure has been observed. A modified regimen with a lower dose lead-in phase may reduce potential saquinavir-/ritonavir-induced QT prolongations.ObjectiveTo explore the effect of the modified saquinavir/ritonavir regimen on QT interval, pharmacokinetics, antiviral activity, and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Ritonavir (norvir), is an HIV protease inhibitor. It works by blocking the growth of HIV [ 8 9 ]. Tiazofurin is a C-nucleoside analogue with antineoplastic activity and acts by inhibition of the guanosine triphosphate (GTP) biosynthesis through a reduction of PI and PIP kinase activity [ 10 – 14 ] ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Ritonavir (norvir), is an HIV protease inhibitor. It works by blocking the growth of HIV [ 8 9 ]. Tiazofurin is a C-nucleoside analogue with antineoplastic activity and acts by inhibition of the guanosine triphosphate (GTP) biosynthesis through a reduction of PI and PIP kinase activity [ 10 – 14 ] ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the patient developed a prolonged QTc interval on her ECG on saquinavir, increasing from 436 to 474 ms. This is a well described side effect of saquinavir and one reason why it no longer a first line PI in HIV-1 treatment [ 39 ]. The decision was taken to switch her PI from saquinavir to darunavir.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained 5 studies which consist of 172 participants that reported about the risk of antivirals in changing QRS wave length (Table 3). [22,24,25,27,29] One study in HIV patients already treated with antiviral drugs reported treatment using ATV/r (300 mg/ 100 mg) could prolong QRS wave length in 2 hours after first dose and persisted after 1 month. [22] Another study in HIV patients treated with NRTI, reported that combination of daily ATV 300 mg, and twice daily LPV/r (400-800 mg/100-200 mg) for 12 to 20 days prolonged QRS wave statistically significant.…”
Section: Effect Of Antiviral Agents Of Interest On Qrs Wavementioning
confidence: 99%